Women’s empowerment in agriculture: What role for food security in Bangladesh? - Sraboni, Esha; Malapit, Hazel J.; Quisumbing, Agnes R.; Ahmed, Akhter (Elsevier, 2014)
Using a nationally representative survey from Bangladesh, we examine the relationship between women’s empowerment in agriculture, measured using the Women’s Empowerment in Agriculture Index, and per capita calorie availability, dietary diversity, and adult body mass index (BMI). Accounting for potential endogeneity of empowerment, we find that increases in women’s empowerment are positively associated with calorie availability and dietary diversity at the household level. Overall, household wealth, education, and occupation are more important than women’s empowerment as determinants of adult nutritional status, although negative impacts of group membership and credit on male BMI suggest that intrahousehold trade-offs may exist.